Perancangan Sistem Informasi Pemesanan Buah Berbasis Web Menggunakan Supply Chain Management Pada PT. Sukses Jaya Segar Sakti Medan - Khotantri, Cindy; Wijaya, Vera; Nasution, Suhendri (Jurnal Mahajana Informasi, 2022)
Progress in the implementation of technology that is increasingly rapid and advanced encourages every business organization to be able to make adjustments to its business transaction activities so as to maximize service to customers. One technology implementation that can be applied to business transaction activities is a web-based ordering information system. PT. Sukses Jaya Segar Sakti is a company that has a business in the field of ordering and distributing fruits to customers. Marketing and ordering fruit to customers is done conventionally by contacting the customer. This study aims to design and build an ordering information system by utilizing a website and using PHP programming and MySql database. The results obtained in this study are an information system capable of supporting business organizations and customers in website-based fruit ordering transaction activities. In addition, the information system built can produce various reports according to needs quickly.